Fast deposition of an ultrathin, highly crystalline organic semiconductor film for high-performance transistors. Issue 7 (19th May 2020) - Zhang, Xiali; Deng, Wei; Lu, Bei; Fang, Xiaochen; Zhang, Xiujuan; Jie, Jiansheng
Abstract : A uniform and smooth Dif-TES-ADT film with thickness of ∼4.62 nm is achieved within 50 s in 2-inch size through the use of a mixed solvent system. The ultrathin Dif-TES-ADT film-based transistors exhibit a maximum mobility up to 5.54 cm 2 V −1 s −1 . Abstract : Ultrathin organic semiconductor (OSC) crystalline films hold the promise of achieving high-performance, flexible, and transparent organic electronic devices. However, fast and high-throughput solution deposition of uniform pinhole-free ultrathin OSC crystalline films over a large area remains a challenge. Here, we demonstrate that a mixed solvent system can obviously alter the fluid flow dynamics and significantly improve the blade-coating quality of the film, enabling us to achieve a large-area continuous and smooth bis(triethylsilylethynyl)anthradithiophene (Dif-TES-ADT) ultrathin film at a fast coating speed of ∼1 mm s −1, much superior to the 30–50 μm s −1 for conventional methods. Also, the ultrathin, highly crystalline Dif-TES-ADT film-based organic thin-film transistors (OTFTs) exhibit a maximum mobility up to 5.54 cm 2 V −1 s −1, which is on par with the Dif-TES-ADT single crystal-based devices and among the highest for Dif-TES-ADT film-based devices. This finding should open a new route to achieve ultrathin OSC crystalline film-based high-performance flexible and transparent electronics.